An Analysis of Teacher’s Oral Corrective Feedback on Student’s Speaking Performance at SMPN 1 Bukittinggi - Regina Henner; Aryuliva Adnan (Journal of English Language Teaching, 2020)
This descriptive research aimed to find out how do English teachers at SMPN 1 Bukittinggi give oral corrective feedback on student’s speaking performance, the ways of teacher giving oral corrective feedback and which types of oral corrective feedback are appropriate and inappropriate. The sample of this research was 4 English teachers at SMPN 1 Bukittinggi. The sample was taken by using total sampling. The techniques of data collection were observation and interview. The instruments used were observation checklist, field note, and audio recording. The data was analyzed based on the theory proposed by Ellis (2009). Based on the findings, it was found that English teachers at SMPN 1 Bukittinggi gave oral corrective feedback in different ways; direct and indirect. Each teacher also had different reasons about the ways they gave oral corrective feedback. Moreover, it was found that each teacher also gave different types of oral corrective feedback. After analyzing the data from the observation and the interview, the types of oral corrective feedback which are appropriate to the students are repetition, explicit correction, and paralinguistic signal. Meanwhile, the types of oral corrective feedback which are inappropriate to the students are recast and clarification request.